DETERMINANTS OF BYOD PROTECTION BEHAVIOR: AN EMPLOYEE'S PERSPECTIVE - Al-Harthy I.M.; Ali N. (Little Lion Scientific, 2023)
Bring Your Own Device (BYOD) allows employees to access the organizational network via their devices/technology. This trend is beneficial to the employees in terms of greater flexibility, apart from productivity and cost savings for the company. Enabling employees to use their own devices at the workplace may lead the company to become vulnerable to information security threats as employees do not possess the right understanding of protecting their devices. This study analyzed the factors that determine employees' behavioral intention and their actual protection behavior in protecting their devices in BYOD environment. A self-administered questionnaire was conducted with 383 government employees in Oman. The results indicated that perceived vulnerability, perceived severity, response cost, subjective norm, perceived behavioral control, and knowledge influenced employees' BYOD intention protection behavior while perceived vulnerability, perceived severity, response efficacy, response cost, attitude, subjective norm, and perceived behavioral control were found to influence BYOD protection behavior. Contrarily, response efficacy, security self-efficacy, attitude, and information security awareness were found to be nonsignificant on protection intention. The findings also revealed that the mediator (protection intention) has a considerable beneficial impact on the dependent variable (protection behavior). Hence, employers should develop an all-encompassing approach to improve their employees' BYOD usage protection behavior to secure the organization's assets. 2022 Little Lion Scientific